Sounds Like Respect. The Impact of Background Music on the Acceptance of Gay Men in Audio-Visual Advertising - Herget, Ann-Kristin; Bötzl, Franziska (Frontiers in Psychology, 2021)
Companies increasingly seek to use gay protagonists in audio-visual commercials to attract a new affluent target group. There is also growing demand for the diversity present in society to be reflected in media formats such as advertising. Studies have shown, however, that heterosexual consumers (especially men), who may be part of the company’s loyal consumer base, tend to react negatively to gay-themed advertising campaigns. Searching for an instrument to mitigate this unwanted effect, the present study investigated whether carefully selected background music can shape the perceived gender of gay male advertising protagonists. In a 2 x 2 between-subjects online experiment (musical connotation x gender of the participant), 218 heterosexual participants watched a commercial promoting engagement rings that featured gay male protagonists, scored with feminine- or masculine-connoted background music. As expected, women generally reacted more positively than men to the advertising. Men exposed to the masculine-connoted background music rated the promoted brand more positively and masculine music also enhanced (at least in the short term) these men’s acceptance of gay men in general (low and medium effect sizes) more than was the case for feminine background music. Carefully selected background music affecting the perceived gender of gay male advertising protagonists may prevent negative reactions from heterosexual audiences and, therefore, motivate companies to use gay protagonists in television commercials on a more regular basis.